Targeting Immune Cells in the Tumor Microenvironment of HCC: New Opportunities and Challenges - Hao, Xiaopei; Sun, Guangshun; Zhang, Yao; Kong, Xiangyi; Rong, Dawei; Song, Jinhua; Tang, Weiwei; Wang, Xuehao (Frontiers in Cell and Developmental Biology, 2021)
Immune associated cells in the microenvironment have a significant impact on the development and progression of hepatocellular carcinoma (HCC) and have received more and more attention. Different types of immune-associated cells play different roles, including promoting/inhibiting HCC and several different types that are controversial. It is well known that immune escape of HCC has become a difficult problem in tumor therapy. Therefore, in recent years, a large number of studies have focused on the immune microenvironment of HCC, explored many mechanisms worth identifying tumor immunosuppression, and developed a variety of immunotherapy methods as targets, laying the foundation for the final victory in the fight against HCC. This paper reviews recent studies on the immune microenvironment of HCC that are more reliable and important, and provides a more comprehensive view of the investigation of the immune microenvironment of HCC and the development of more immunotherapeutic approaches based on the relevant summaries of different immune cells.